Narration in Elyas Khouri’s Novel Bab E-Shams - Amal Ahmad Abid Al-Lateef Ahmad (My University, 2005)
This study debates a world novelist, perhaps one of the most important figures in Arabic fiction. He is Elyas Khouri. The study dwells on the levels of intertextuality in his novel Bab e-Shams published in 1998. According to some critics, this work was a qualitative leap in fiction writing. Khouri himself considered it the most significant turning point in the history of his fiction writing. The intertextuality phenomenon in Bab e-Shams was not studied before although several scholars and critics have written about Khouri’s works. To hold intertextuality comparisons in Bab e-Shams, the researcher depended on intertextuality method, making active use of western critical studies, which "proselytized"for this intertextuality term, and Arab scholars’ works on this term such as those of Sa’id Yaqteen in Infitah a-Nuss e-Riwa’i: Enuss w-Siyaq, Mohammed Moftah in Tahlil al-Khitab a-Shi’ri: Istratijeyat Ettanass. This was in addition to reader response theories. Against this background, the researcher concluded by reading the intratextuality, intertextuality and externaltextuality, in Bab e-Shams, through identification of the extent of other texts’ presence or absence in the narrative text. To this end, the researcher searched for the original sources and the role they played in formation of meaning inside the novel and the extent of the writer’s benefit from them, thus helping us, in the end, to dwell on the influence of anxiety which motivated the writer to practice these narrative interrelationships. This study included, in addition to an introduction, three chapters and a conclusion. In the introduction, the researcher justified her choice of intertextuality in Bab e-Shams in addition to definition of intertextuality approach and the contents of the study. In chapter one, the researcher examined intratextuality, i.e. the link of the writer’s Bab e-Shams with his other novels. This was, however, restricted to stylistic intertextuality with the writer’s other novels in which the style seemed similar to some extent in terms of overlapping of narratives and repetition, style of negation and similarity between the narrator and the novelist, multi-narrators and narrative playing, splitting of self and overlapping of intertextuality pronouns. In chapter two, the researcher tackled intertextuality, i.e. the link of the novel with contemporary texts from Arabic and world literature and history. Given the plethora of these intertextuality models, the researcher highlighted the most prominent, whether in the body of the text or in its memory-in absent texts. At the level of literary intertextuality, chapter two included intertextuality with Paula as a model of world novel and intertextuality with A’id Ila Haifa as a representative of the Arab novel. In modern Arabic poetry, the researcher examined intertextuality in Mahmoud Darwish, and Al-Akhtal a-Saghir; she also examined intertextuality in Jan Jeane’s memoirs Aseer Ashiq and Araba’ Sa’at in Shatila. Concerning intertextuality in non-literary text (historical and documentary texts), the researcher depended on Amnon Kapliuk’s Tahqiq Hawla Majzara. In the last chapter, the researcher examined external intertextuality, i.e., the link of the novel with other texts which belonged to the distant past. The chapter included mythical intertextuality. The Odyssey was taken as a representative work, the religious intertextuality (Islamic and New Testament) and intertextuality in ancient Arabic poetry. Representatives were Imru’ el-Qais, al-Mutanabi, Abu Tamam, and Majnoon Laila. Intertextuality in folkloric narrative texts was represented by Alf Lailah w-Lailah (one Thousand and One Night). For intertextuality with drama, the researcher used Shakespeare’s Hamlet. In the conclusion, the researcher summed up the results of her study, the justifications for employing intertextuality between the novel and other examined texts.

تتناول هذه الدراسة التناص في رواية إلياس خوري "باب الشمس"، وذلك من خلال الوقوف على مستويات التناص: الذاتي والداخلي والخارجي، عبر الكشف عن مدى حضور النصوص الأخرى أو غيابها في النص الروائي، والدور الذي تلعبه في تشكيل المعنى داخل الرواية ومدى إفادة الكاتب منها. تشتمل الدراسة على مقدمة وثلاث فصول وخاتمة. تناولت الباحثة في المقدمة أسباب اختيارها لموضوع التناص في رواية "باب الشمس"، إضافة إلى التعريف بمنهج التناص وبمحتويات الدراسة. تتناول الباحثة في الفصل الأول التناص الذاتي، أي صلة الرواية بروايات الكاتب الأخرى، واقتصر هذا الجانب على التناص الأسلوبي مع بعض روايات الكاتب التي بدا فيها الأسلوب متشابهاً إلى حد ما. وذلك من حيث تداخل الحكايات، والتكرار، وأسلوب النفي، والتشابه بين السارد والروائي، وتعدد الرواة، واللعب الروائي، وانشطار الذات، وتداخل ضمائر السرد. وفي الفصل الثاني تتناول الباحثة التناص الداخلي، أي صلة الرواية مع نصوص معاصرة من الأدب العربي والعالمي والتاريخي، ولكثرة هذه النماذج التناصية اقتصرت الباحثة على أبرزها حضوراً، إن كان في جسد النص أم في ذاكرتها أي –النصوص الغائبة-. فالتناص الأدبي، شمل التناص مع رواية "باولا" نموذجاً للتناص مع الرواية العالمية، والتناص مع "عائد إلى حيفا" نموذجا للتناص مع الرواية العربية، وكذلك التناص مع الشعر العربي الحديث من خلال التناص مع محمود درويش، والأخطل الصغير، والتناص مع مذكرات (جان جينيه) "أسير عاشق" و "أربع ساعات في شاتيلا". أما التناص مع النصوص غير الأدبية (النص التاريخي والوثائقي)، فجاء من خلال كتاب تحقيق حول مجزرة (لأمنون كابليوك). وفي الفصل الأخير الذي جاء بعنوان التناص الخارجي، تناولت الباحثة صلة الرواية مع نصوص أخرى ظهرت في عصور بعيدة وشمل هذا الفصل: التناص الأسطوري مع الأودية نموذجاً، والتناص الديني (الإسلامي، والعهد الجديد)، والتناص مع الشعر العربي القديم ممثلاً: بإمرئ القيس، والمتنبي، وأبي تمام، ومجنون ليلى، وكذلك التناص مع النص السردي التراثي ممثلاً بـ "ألف ليلة وليلة"، إضافة إلى التناص مع مسرحية "هاملت". وتأتي الخاتمة في نهاية الدراسة لتخلص رؤية الباحثة حول كل ما تم دراسته، وذلك من خلال عرضها للنتائج التي توصلت إليها، مكثفة مسوغات التناص بين الرواية والنصوص المدروسة الأخرى.
التناص في رواية إلياس خوري باب الشمس